Effectiveness Of Digital Text in Interactive Library for English Starters (Digi-Tiles in Enhancing The Reading Comprehension Of Grade 3 Learners) - Laroza, Jujie (Faculty of Teacher Training and Education, Universitas Terbuka, 2023)
This quasi-experimental study was conducted to measure the effectiveness of Digital Text in Interactive Library for English Starters (Digi-TILES), which is a digital learning tool, in improving the reading comprehension level of Grade 3 pupils of Sampiruhan Elementary School. The intervention tool was designed to develop reading comprehension of learners and results were measured through comparing pretest and post-test scores.Two (2) paired groups of learners participated in the study composed of 30 members for each group. Each group’s reading comprehension level was determined through standardized Phil-IRI materials. The digital tool intervention developed by the researcher was utilized by the experimental group while the comparison group utilized plain printed Pivot Self Learning Modules distributed by Department of Education. Paired and Independent Samples T-tests were used to answer the inferential questions of the study.The experimental group, after utilizing the intervention tool scored higher in their post-test than the comparison group. Comparing also the pretest and post-test of the experimental group, it is notable that the scores in the latter are significantly higher. This implies that the Digi-TILES learning tool has impacted the learners’ reading comprehension positively.The hypotheses stating that there is no significant difference between the post-test of the two groups were rejected. The findings therefore reflect that the experimental group scored higher those in the comparison group. The Digi-TILES therefore helped in enhancing the reading comprehension of Grade 3 learners. It is therefore suggested that the school may consider utilizing this tool to improve the quality of learners when it comes to reading comprehension.